Fracture Strength and Marginal Adaptation of Conservative and Extended MOD Cavities Restored with Cention N - Maryam Firouzmandi; Ali Asghar Alavi; Dana Jafarpour; Soroush Sadatsharifee (International Journal of Dentistry)
The aim of the present study was to compare the fracture strength and marginal adaptation of MOD cavities restored with Cention N, bonded Cention N, and resin composite, as well as to investigate the effect of cavity preparation volume on those properties. In this experimental study, 120 human maxillary premolars were randomly divided into six groups according to the type of restoration and cavity volume (n = 20): (I) conservative MOD restored with Cention N, (II) conservative MOD restored with bonded Cention N, (III) conservative MOD restored with Z250 resin composite, (IV) extended MOD restored with Cention N, (V) extended MOD restored with bonded Cention N, and (VI) extended MOD restored with Z250 resin composite. Fracture strength (MPa) was tested using a universal testing machine. To investigate marginal adaptation, polyvinyl-siloxane impressions were taken and poured with epoxy resin. Resin replicas were examined by SEM (×400) for marginal adaptation. ANOVA tests, Tukey’s test, and independent t-test were used to analyze data (P ≤ 0.05). Among conservative restorations, the fracture strength of bonded Cention N was significantly greater than that of Cention N (P = 0.001), while in the extended preparations, there was no significant difference between fracture strengths of different types of restorations (P = 0.579). In terms of marginal adaptation, there was no significant difference between different types of conservative restorations (P = 0.232). However, in extended preparations, composite showed significantly lower marginal adaptation than Cention N and bonded Cention N (P = 0.004 and P = 0.045, respectively). Conservative preparations showed significantly greater fracture strength and marginal adaptation compared to extended ones in groups restored with composite. The volume of cavity preparation was shown to be effective in the materials fracture strength and marginal adaptation. Cention N showed promising results in terms of fracture strength and marginal adaptation.